The Representation of Gender Inequality Toward Female Characters In Sasti Gotama’s Novel Korpus Uterus: A Norman Fairclough Critical Discourse Analysis Perspective - Mayada Mayada; Eko Hardinanto; Ahmad Faizi (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2026)
Literature is a product of human thought that originates from individuals and derives from the surrounding social environment. The purpose of this study is to reveal the representation of gender inequality toward female characters in Sasti Gotama's novel Korpus Uterus. The focus of this study lies in three aspects, namely textual analysis, text interpretation, and text explanation. The data source of this study is the novel Corpus Uterus by Sasti Gotama. The data consists of excerpts in the form of phrases, clauses, words, and paragraphs found to be relevant within the novel. The data analysis technique employed in this study is descriptive qualitative analysis. Meanwhile, the data were collected through reading and note-taking techniques. This study adopts a qualitative approach. The findings indicate that, at the textual level, the novel employs diction closely associated with the medical field. This is inseparable from the author's professional background as a physician. In addition, the use of such objects is related to trauma, marginalization, and subordination, all of which signify forms of gender inequality. In terms of text production, the author utilizes her knowledge and professional background to deconstruct narratives of injustice that have long constrained women. Through this strategy, the author encourages readers not only to empathize with the characters' trauma but also to think critically about the experiences that surround them. Furthermore, the explanatory dimension of the text reflects the reality in Indonesia, where gender inequality experienced by women through patriarchal hegemony remains deeply entrenched and persistent.